A Comprehensive Review of Sarcoidosis: From Clinical Manifestations to Management Strategies - Olga Śpiołek; Jan Siwiec; Aleksandra Słowikowska; Mateusz Teofilak; Julia Szatkowska; Natalia Smyl; Marcelina Sztyler-Krąkowska; Agnieszka Wąsowicz; Franciszek Kędziora; Dariusz Fabian (Journal of Education, Health and Sport)
Introduction and purpose: Sarcoidosis is a complex, multi – system disease characterized by the formation of non – caseating granulomas that can affect nearly every organ in the body, though lungs and lymph nodes are the most commonly involved. The disease's clinical presentation is highly variable, ranging from asymptomatic cases to severe, organ-threatening manifestations, with significant implications for diagnosis and treatment.  The aim of this study is to present current state of knowledge on clinical features, etiology, diagnosis and treatment methods of sarcoidosis.